Etiology analysis and G6PD deficiency for term infants with jaundice in Yangjiang of western Guangdong - Yang, Yi-Kang; Lin, Chun-Fan; Lin, Fen; Chen, Zi-Kai; Liao, Yu-Wei; Huang, Yu-Chan; Xiao, Bei-Ru; Huang, Shan-Hua; Xu, Yu-Mei; Chen, Yue-E.; Cao, Yan-Bin; Yang, Li-Ye (Frontiers in Pediatrics, 2023)
Objective: Glucose 6-phosphate dehydrogenase (G6PD) deficiency increases the risk of neonatal hyperbilirubinemia. The aim of this study is to evaluate the risk factors associated with hyperbilirubinemia in infants from the western part of Guangdong Province, and to assess the contribution of G6PD deficiency to neonatal jaundice.The term infants with neonatal hyperbilirubinemia in People's Hospital of Yangjiang from June 2018 to July 2022 were recruited for the retrospective analysis.All the infants underwent quantitative detection of the G6PD enzyme. The etiology was determined through laboratory tests and clinical manifestations.Results: Out of 1119 term infants, 435 cases presented with jaundice. For the etiology analysis, infection was responsible for 16.09% (70/435), G6PD deficiency accounted for 9.66% (42/435), of which 3 were complicated with acute bilirubin encephalopathy), bleeding accounted for 8.05% (35/435), hemolytic diseases accounted for 3.45% (15/435), and breast milk jaundice accounted for 2.53% (11/435).One case (0.23%) was attributed to congenital hypothyroidism, multiple etiologies accounted for 22.3% (97/435), and 35.63% (155/435) were of unknown etiology. Of the jaundiced infants, 19.54% (85/435) had G6PD deficiency, while only 10.23% (70/684) of non-jaundiced infants had G6PD deficiency; this difference was found to be statistically significant (P＜0.001). Furthermore, the hemoglobin levels in the jaundiced infants with G6PD deficiency (146.85±24.88 g/L) were lower than those without G6PD deficiency (156.30±22.07 g/L) (P=0.001). 65 jaundiced infants with G6PD deficiency underwent G6PD mutation testing, and six different genotypes were identified, including c.95A＞G, c.392G＞T, c.1024C＞T, c.1311C＞T, c.1376G＞T, c.1388G＞A, c.871G＞A/c.1311C＞T, c.392G＞T/c.1388G＞A, and c.1376G＞ T/c.1311C＞T.65iciency Conclusion: In newborns in Yangjiang, G6PD deficiency, infection, and neonatal hemolytic disease were identified as the main causes of hyperbilirubinemia and acute bilirubin encephalopathy. Specifically, hemolytic factors in infants with G6PD deficiency may lead to reduced hemoglobin and increased bilirubin levels in jaundiced infants.